The Prospect of Independent Banking Ombudsman in Indonesia: An Institutional Analysis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Abstract Since 30June 2006, the National Banking Ombudsman/Mediation function has been performed by Central Bank. However, it is put forward that no later than 31 December 2007, the ombudsman scheme shall be conducted by independent body formed under the aegis of Banking Association (PBI No.8/5/2006 article 3). This brings new problem whether the current Banking Ombudsman is well prepared for the transition from Statutory Ombudsman Scheme (by central bank) to Voluntary Ombudsman Scheme (by bank association and consumer representatives). The paper assesses the prospects of current banking ombudsman of Indonesia to advance into voluntary/independent banking ombudsman scheme. It utilizes the combinative methodology of Institutional Analysis and Development (lAD) Framework and Pakpahan (1991) institutional aspects to evaluate the feasibility of transition. We find out that with the prevailing level of institutional aspects (regulative, coordinative, human resource, transparency and society participation aspects), the feasible model is two-tier ombudsman scheme. Nevertheless, to get into with the new scheme, bank associations and other participants need to summon the initiatives of their members and rectify their institutional infrastructure